Organ Function Preservation Failure after (Chemo)Radiotherapy in Head and Neck Cancer: A Retrospective Cohort Analysis. (7th May 2019) - Heukelom, Jolien; Navran, Arash; Gouw, Zeno A. R.; Tesselaar, Margot E.; Zuur, Charlotte L.; van Werkhoven, Erik; Sonke, Jan‐Jakob; Rasch, Coen R. N.; Al‐Mamgani, Abrahim
Abstract : Objective: The aim of the current study was to determine the incidence of organ function preservation failure (OFPF) in patients with head and neck squamous cell carcinoma (HNSCC) treated by (chemo)radiotherapy and to identify its risk factors. Study Design: Retrospective cohort analysis. Setting: Tertiary cancer care center. Subjects and Methods: A single‐center retrospective cohort analysis was done (n = 703) in which OFPF after (chemo)radiotherapy was assessed. OFPF was defined as local failure or pure functional failure in the absence of local failure because of major surgical intervention (total laryngectomy, commando resection, permanent tracheostomy) or feeding tube dependence >2 years. Results: OFPF occurred in 153 patients (21.8%). Reasons for OFPF were local failure in 103 patients (14.6%) and functional failure in 50 patients (7.2%). Evidence of functional failure included need for total laryngectomy (n = 9, 1.3%), commando resection (n = 2, 0.3%), permanent tracheostomy (n = 16, 2.3%), and/or long‐term feeding tube for functional reasons (n = 23, 3.3%). In a Cox proportional hazards model, OFPF was worse for patients with T4 tumors (hazard ratio [HR] <0.5 and P <. 001 for all other stages), for laryngeal vs oropharyngeal cancer (HR, 1.83; 95% confidence interval [CI], 1.20‐2.79, P =. 005, hypopharyngeal not significant), and for smokers (HR, 1.68; 95% CI, 1.10‐2.56, P =. 015). Exploratory multivariate analysis by tumor site showed that T4 tumor and pretreatment tracheostomy were the strongest predictive factors for OFPF in laryngeal and hypopharyngeal carcinoma while T4 tumor and smoking were predictive for poor OFPF in oropharyngeal carcinoma. Conclusion: This work shows a detrimental effect of smoking on functional outcomes after (chemo‐)radiotherapy for HNSCC. Moreover, T4 tumor, laryngeal subsite, and pretreatment tracheostomy are strong predictors of OFPF.